2022
DOI: 10.7759/cureus.22698
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sphincterotomy for Cholecysto-Choledocholithiasis Complicates Subsequent Laparoscopic Cholecystectomy: A Retrospective Report From Sri Lanka

Abstract: Objective: Published literature so far has supported the fact that patients who underwent endoscopic retrograde cholangio-pancreatography and sphincterotomy (ERCPS) had a difficult perioperative course after subsequent laparoscopic cholecystectomy. Through a retrospective study, this original report mentions statistics in a Southeast Asian population comparing the effect on conversion to open surgery in patients undergoing laparoscopic cholecystectomy after ERCPS in a university hospital in Sri Lanka.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Currently, the known incidence of recurrent common bile duct stones after undergoing ERCP ranges from 7–21% [ 3 ]. The main cause of recurrent common bile duct stone development after ERCP is the reflux of duodenal contents into the biliary system, leading to bacterial colonization and subsequent stone formation [ 2 , 4 , 5 ]. Studies have shown that excessively large or numerous common bile duct stones can lead to the failure of ERCP procedures, resulting in unnecessary financial and psychological burden for patients [ 6 ].…”
mentioning
confidence: 99%
“…Currently, the known incidence of recurrent common bile duct stones after undergoing ERCP ranges from 7–21% [ 3 ]. The main cause of recurrent common bile duct stone development after ERCP is the reflux of duodenal contents into the biliary system, leading to bacterial colonization and subsequent stone formation [ 2 , 4 , 5 ]. Studies have shown that excessively large or numerous common bile duct stones can lead to the failure of ERCP procedures, resulting in unnecessary financial and psychological burden for patients [ 6 ].…”
mentioning
confidence: 99%